From wedding guest to bride? - Beckett, Tina (Night Shift in Barcelona, 2022)
When wedding guest Elena shares a mind-blowing kiss with sexy stranger Santiago, it's wholly out of character for the diagnostician ... Elena shut her heart off to love when her childhood sweetheart walked away just as she faced a life-changing diagnosis. Still, she can't deny how refreshing it is to be with widower Santiago, who understands heartache more than anyone. Will he become her heart's safe haven?